Pengaruh Kompensasi, Beban Kerja dan Komitmen Kerja Terhadap Turnover Intention Karyawan Dengan Worklife Balance Sebagai Variabel Mediasi - Lili Jumiati; Fiko Farlis (Jurnal Ekonomika Dan Bisnis (JEBS), 2026)
This research is motivated by the phenomenon of many employees of PT Gratama Finance Pekanbaru who left their jobs as employees or turnover intention during the last 5 years, namely 2020-2024. This study aims to determine the effect of Compensation, Workload and Work Commitment on Turnover Intention with Worklife Balance as a mediating variable on Employees of PT Gratama Finance Pekanbaru. This type of research is quantitative. The population and sample of the study were 50 respondents. Data were obtained using primary questionnaire data and then analyzed using the PLS-SEM method using the PLS-SEM Partial Least Squares Structural Equation Modeling program). The results showed that Compensation had a significant negative effect on turnover intention. Workload had a positive effect on turnover intention. Work commitment had a negative effect on turnover intention. Compensation had a positive effect on worklife balance. Workload had a significant negative effect on worklife balance. Work commitment had a positive effect on worklife balance. The mediation test showed that work-life balance acts as a mediator between compensation and turnover intention. Workload has an indirect effect on turnover intention through work-life balance. Work commitment has an indirect effect on turnover intention through work-life balance. The conclusion of this study is that all exogenous variables influence endogenous variables, both directly and indirectly.